SISTEM INFORMASI MOBILE "HARRIS WORK REQUEST" BERBASIS ANDROID UNTUK OPTIMALISASI PERMINTAAN PEKERJAAN PADA HOTEL HARRIS SENTUL CITY BOGOR - Daniel Recksa Yudda (2022)
Hotel Harris is one of the hotel brands owned by Tauzia management with a four-star standard with various facilities such as rooms, meeting rooms, swimming pools, and several other recreational facilities. Hospitality is a business with a dynamic work system or work on demand. With many facilities and crowded hotel visitors, management often experiences problems, one of them is slow handling problem by a department, both handling visitors' problem and other departments problem. At this time, smartphones are widely used by most people, including the employees of Hotel Harris Sentul City Bogor, the majority of whom use smartphones with the Android operating system. With such conditions, it is necessary to create an Android-based Harris Work Request mobile information system that can record the details of the work queues of each department that are requested by other departments every day. The Android-based Harris Work Request mobile information system that the author created is expected to be able to optimize the work requested from each department by providing more detailed information about when and by whom the work was requested, the time limit for doing the work, and when and by whom the work was completed. The information system can also automatically create a weekly chart (per seven days) of each job request by entering the date as a reference for the chart time range. The diagram can be used by management leaders to evaluate the performance of their employees. In addition, the information system is also equipped with additional features, namely News, Broadcast Chat, Personal Chat, and Harris Café Counter.